Teaching Poetry Appreciation in Higher Education: A Systematic Review of Innovative Approaches - Nazriani, Nazriani; Munirah, Munirah; Akhir, Muhammad (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
Poetry appreciation learning in college shows a shift from textual analysis to a more integrative and student-centered approach. This study uses the Systematic Literature Review method of 18 articles indexed by Scopus and SINTA (2021–2025) using the framework of Cabrera & Cabrera (2023). The results of the synthesis identified four innovative approaches, namely HOTS-based learning, character education through poetic inquiry, digital technology integration, and contextual and multisensory approaches. These four approaches have been proven to improve students’ critical thinking skills, reflective capacity, empathy, creativity, and aesthetic sensitivity. The main contribution of this study is the formulation of the Integrative Model of Poetry Appreciation (MIAP), a new conceptual model that combines cognitive, affective, technological, and aesthetic experience dimensions as the basis for the development of a more holistic poetry pedagogy. These findings confirm the importance of TPACK competencies and integrative learning designs that are able to facilitate a balanced cognitive, emotional, and multisensory learning experience.